Biosensor‐assisted engineering of a high‐yield Pichia pastoris cell‐free protein synthesis platform. Issue 3 (11th January 2019) - Aw, Rochelle; Polizzi, Karen M.
Abstract: Cell‐free protein synthesis (CFPS) has recently undergone a resurgence partly due to the proliferation of synthetic biology. The variety of hosts used for cell‐free extract production has increased, which harnesses the diversity of cellular biosynthetic, protein folding, and posttranslational modification capabilities available. Here we describe a CFPS platform derived from Pichia pastoris, a popular recombinant protein expression host both in academia and the biopharmaceutical industry. A novel ribosome biosensor was developed to optimize the cell extract harvest time. Using this biosensor, we identified a potential bottleneck in ribosome content. Therefore, we undertook strain engineering to overexpress global regulators of ribosome biogenesis to increase in vitro protein production. CFPS extracts from the strain overexpressing FHL1 had a three‐fold increase in recombinant protein yield compared with those from the wild‐type X33 strain. Furthermore, our novel CFPS platform can produce complex therapeutic proteins, as exemplified by the production of human serum albumin to a final yield of 48.1 μg ml −1 . Therefore, this study not only adds to the growing number of CFPS systems from diverse organisms but also provides a blueprint for rapidly engineering new strains with increased productivity in vitro that could be applied to other organisms. Abstract : Aw and Polizzi developed a cell‐free protein synthesis (CFPS) system based on extracts from the industrially relevant yeast, Pichia pastoris. Genetically‐encoded biosensors were used to determine the optimal harvest time and screen engineered strains for sustained ribosome content. Overexpression of a single transcription factor led to a 3‐fold increase in recombinant protein yield. The work adds to the growing number of CFPS systems from diverse organisms and also provides a blueprint for rapidly engineering new strains with increased CFPS productivity.